The longitudinal relation between social reserve and smaller subsequent decline in executive functioning in old age is mediated via cognitive reserve. (23rd May 2021) - Ihle, Andreas; Oris, Michel; Baeriswyl, Marie; Zuber, Sascha; Cullati, Stéphane; Maurer, Jürgen; Kliegel, Matthias
ABSTRACT: Objectives: Social reserve such as having close friends helps promoting activity engagement in old age. Activity engagement in turn contributes to the accumulation of cognitive reserve and is a key predictor for maintaining executive functioning in aging. We investigated the mediating role of leisure activity engagement in the longitudinal relation between close friends and subsequent change in executive functioning as measured through performance changes in the Trail Making Test (TMT). Design, Setting, and Participants: Longitudinal study with 897 older adults tested in two waves 6 years apart, analyzed using latent change score modeling. Measurements: TMT parts A and B, leisure activity engagement, and close friends. Results: A larger number of close friends in the first wave of data collection was related to a higher frequency of leisure activities in the first wave. A higher frequency of leisure activities in the first wave significantly predicted a smaller subsequent increase in TMT completion time from the first to the second wave (i.e. a smaller decline in executive functioning). Importantly, 41.3% of the longitudinal relation between a larger number of close friends in the first wave and a smaller subsequent increase in TMT completion time (i.e. a smaller decline in executive functioning) was mediated via a higher frequency of leisure activities in the first wave. Conclusions: Social reserve such as having close friends may help promoting activity engagement in old age. By enhancing individuals' cognitive reserve, this activity engagement may finally result in smaller subsequent decline in executive functioning in aging.